2012
DOI: 10.1074/jbc.m112.339622
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mesenchymal Stem and Progenitor Cells from Bone Marrow Lack Expression of CD44 Protein

Abstract: Background:The natural phenotype of mesenchymal stem cells (MSCs) has not been well characterized. Results: MSCs from bone marrow naturally are CD44 Ϫ ; however, in vitro cultivation results in acquisition of CD44 expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
133
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(148 citation statements)
references
References 49 publications
11
133
3
1
Order By: Relevance
“…CD44 is a well-described adhesion molecule existing in different isoforms that interact with multiple ligands, such as hyaluronan, selectins, collagen and fibronectin, but the functional consequence for acquisition of CD44 expression on the expanded MSC during therapeutic use remains unclear (9). Qian et al provide functional and molecular evidence suggesting that MSC physiologically do not express CD44 in both humans and mice and confirm that in vitro culture could result in acquisition of CD44 expression on their surface and changes in the expression of cytokines, growth factors, matrix proteins and other signaling molecules (9). In this context, the absence of the CD44 expression in MSC, after implantation onto CAM, represents a proof that MSC regain their precultivation CD44 status when they re-enter the in vivo medium.…”
Section: Discussionmentioning
confidence: 92%
“…CD44 is a well-described adhesion molecule existing in different isoforms that interact with multiple ligands, such as hyaluronan, selectins, collagen and fibronectin, but the functional consequence for acquisition of CD44 expression on the expanded MSC during therapeutic use remains unclear (9). Qian et al provide functional and molecular evidence suggesting that MSC physiologically do not express CD44 in both humans and mice and confirm that in vitro culture could result in acquisition of CD44 expression on their surface and changes in the expression of cytokines, growth factors, matrix proteins and other signaling molecules (9). In this context, the absence of the CD44 expression in MSC, after implantation onto CAM, represents a proof that MSC regain their precultivation CD44 status when they re-enter the in vivo medium.…”
Section: Discussionmentioning
confidence: 92%
“…As previous research has shown, CD44 -MSCs exhibit similar properties to MSCs (12). Thus, to analyze Sca-1 expression, the CD45 -CD31 -CD44 -Sca-1 + MSCs were sorted.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experimental protocols were performed with approval from the Local Ethics Committee at Karolinska Institute. Mononuclear cells were isolated from the BM of the mice using a previously described method (12). Briefly, femurs, tibias and iliac crests were crushed in Dulbecco's phosphate-buffered saline (DPBS; Gibco Life Technologies, Paisley, Scotland) and 10% fetal bovine serum (FBS; #10500064; Gibco Life Technologies, Divinopolis, Brazil).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations